Occupational Risk Factors for Kidney Disease: A Comprehensive Review - Park, Min Young; Kang, Mo-Yeol (Journal of Korean medical science, 2025)
Chronic kidney disease (CKD) is a major global health concern, with traditional risk factors such as diabetes and hypertension well established. However, emerging evidence suggests that occupational exposures could play a significant role in CKD development. This review comprehensively summarizes the current evidence concerning occupational risk factors contributing to kidney disease, including exposure to heavy metals (lead, cadmium, mercury, chromium), organic solvents (trichloroethylene, methanol, ethylene glycol), heat stress, and job-related stress factors (occupational stress, long working hours, shift work). Epidemiological studies indicate that nephrotoxic agents contribute to renal dysfunction through oxidative stress, mitochondrial damage, and impaired ion transport. Industries such as manufacturing, agriculture, and mining pose particularly high risks due to hazardous exposures. While strong evidence links nephrotoxic metals and solvents to early renal dysfunction, the long-term effects of chronic low-dose exposure remain unclear. Additionally, heat stress-related CKD, particularly Meso-American nephropathy, highlights the growing concern of climate-related occupational risks. Job-related stress factors, including long working hours and shift work, may further accelerate CKD progression through stress-induced hypertension and metabolic disturbances. Given the substantial public health implications, preventive strategies should focus on reducing workplace exposures, implementing heat stress management programs, and addressing the impact of job-related stress factors.